Nutrition intervention in heart failure: should consumption of the DASH eating pattern be recommended to improve outcomes? - Abu-Sawwa, Renad (Heart Fail Rev, 2019)
Heart failure (HF) is a chronic, systemic disorder that presents a serious and growing public health problem due to its high prevalence, mortality, and cost of care. Due to the aging of the population and medical advances that prolong the life of HF patients, more effective, widespread strategies for improved HF management in this rapidly growing patient population are needed. While the prevalence of malnutrition in HF patients has been well characterized, evidence is limited regarding the effects of specific macro- and micronutrient deficiencies on HF outcomes and their interaction with other aspects of HF management, including pharmacotherapy. There is a mounting appreciation for the effects of nutritional intervention on pathophysiology, treatment, and outcomes in patients with HF. Heart-healthy dietary patterns, such as the Dietary Approaches to Stop Hypertension (DASH), carry importance for the prevention and treatment of hypertension. While preliminary evidence looks promising regarding effects of DASH eating pattern consumption on ventricular function and 30-day hospitalizations in HF patients, more research is needed to confirm its effects on short-term and long-term HF outcomes while better understand underlying mechanisms in the context of HF pharmacotherapy.